Tropomyosin isoforms bias actin track selection by vertebrate myosin Va - Sckolnick, Maria (Mol Biol Cell, 2016)
Tropomyosin (Tpm) isoforms decorate actin with distinct spatial and temporal localization patterns in cells and thus may function to sort actomyosin processes by modifying the actin track affinity for specific myosin isoforms. We examined the effect of three Tpm isoforms on the ability of myosin Va (myoVa) to engage with actin in vitro in the absence or presence of the cargo adapter melanophilin (Mlph), which links myoVa to Rab27a-melanosomes for in vivo transport. We show that both the myosin motor domain and the cargo adapter Mlph, which has an actin-binding domain that acts as a tether, are sensitive to the Tpm isoform. Actin–Tpm3.1 and actin–Tpm1.8 were equal or better tracks compared to bare actin for myoVa-HMM based on event frequency, run length, and speed. The full-length myoVa-Mlph complex showed high-frequency engagement with actin-Tpm3.1 but not with actin-Tpm1.8. Actin–Tpm4.2 excluded both myoVa-HMM and full-length myoVa-Mlph from productive interactions. Of importance, Tpm3.1 is enriched in the dendritic protrusions and cortical actin of melanocytes, where myoVa-Mlph engages in melanosome transport. These results support the hypothesis that Tpm isoforms constitute an “actin–Tpm code” that allows for spatial and temporal sorting of actomyosin function in the cell.